2014
DOI: 10.1088/1054-660x/24/11/115302
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Stokes-enhanced tunnelling ionization of polar molecules

Abstract: We generalize the correct account for molecule vibrational motion in tunnelling ionization, proposed earlier (Kornev and Zon 2012 Phys. Rev. A 86 043401), to the case of polar molecules. We consider the tunnel effect in both dc and ac fields, taking into account perturbation of vibrational motion by an external field. We develop a method for accounting for dipole moment on the base of the electronic wave function expansion over dipole-spherical functions instead of ordinary spherical functions. The change of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 72 publications
(194 reference statements)
0
22
0
Order By: Relevance
“…Alternatively, based on the MO-ADK model, Zon et al proposed an anti-stokes-enhanced tunneling ionization (ASETI) method to investigate the effect of vibrational motion on the strong field ionization of molecules. [27][28][29] In their method, the Dyson orbital wavefunctions including nuclear motion are used as the molecular wavefunctions, and the ionization rate of molecules in the TI regime is described by the combination of the Frank-Condon factors between the neutral and ionic electronic states and the ADK ionization rate, which is dependent on the ionization potential. [27][28][29] According to this ASETI model, we can qualitatively understand the experimental observation in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, based on the MO-ADK model, Zon et al proposed an anti-stokes-enhanced tunneling ionization (ASETI) method to investigate the effect of vibrational motion on the strong field ionization of molecules. [27][28][29] In their method, the Dyson orbital wavefunctions including nuclear motion are used as the molecular wavefunctions, and the ionization rate of molecules in the TI regime is described by the combination of the Frank-Condon factors between the neutral and ionic electronic states and the ADK ionization rate, which is dependent on the ionization potential. [27][28][29] According to this ASETI model, we can qualitatively understand the experimental observation in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…According to our calculations, the initial population ratio in the X 2 Σ + and A 2 Π states of CO + is about 100:1. The ionization probability of removing one electron from HOMO (σ symmetry) of CO is maximal when the molecular axis is parallel to the laser field, while removing one electron from HOMO-1(π symmetry) of CO the ionization probability is maximal when the molecule axis perpendicular to the polarization of the laser field [13,14]. For the dissociation process, we numerically solved the time dependent Schrödinger equation (for details of the model please see Ref [7].).…”
Section: Numerical Simulations and Discussionmentioning
confidence: 99%
“…For the single ionization of a molecule, as described by the strong-field approximation [8] or molecular orbital Ammosov-Delone-Krainov theories [9,10], and numerically simulated by solving the timedependent Schrödinger equation [11,12], electrons are favored to be freed by the laser field pointing along the maximal density distributions of the ionizing orbital, i.e. selective ionization of molecule with a given spatial orientation correlated to the orbital profile [13,14]. Although most of the models are based on the single-active-electron approximation by assuming tunneling ionization from the highest occupied molecular orbital (HOMO) [12], for a molecule with multiple electrons, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The x2dhf program was also used by Grabo and Gross for optimized effective potential calculations within the KLI approximation, 596,597 by Karasiev and coworkers for density functional development, [598][599][600][601][602][603][604][605][606] by Halkier and Coriani for computing molecular electric quadrupole moments, 607 Roy and Thakkar who studied MacLaurin expansions of the electron momentum density for 78 diatomic molecules, 608 Weigend, Furche, and Ahlrichs for studying total energy and atomization energy basis set errors in quadruple-ζ basis sets, 609 Shahbazian and Zahedi who studied basis set convergence patterns, 610 Pruneda, Artacho, and Kuzmin for the calculation of range parameters, [611][612][613] Madsen and Madsen for modeling high-harmonic generation, 614 Williams et al who reported numerical HF energies for transition metal diatomics, 615 Madsen and coworkers who calculated structure factors for tunneling, [616][617][618][619] Kornev and Zon who studied anti-Stokes-enhanced tunneling ionization of polar molecules, 620 and Endo and coworkers who studied laser tunneling ionization of NO. 621 Based on the results of Laaksonen et al, Kolb and coworkers developed a FEM program for HF and density functional calculations employing triangular basis functions, again in the (µ, ν) coordinate system.…”
Section: Diatomic Moleculesmentioning
confidence: 99%